New records of Pteridophytes for Kashmir Valley, India - SHAKOOR A. MIR; ANAND K. MISHRA; ZAFAR A. RESHI; M. P. SHARMA (Biodiversitas Journal of Biological Diversity, 2014)
Mir SA, Mishra AK, Reshi ZA, Sharma MP. 2014. New Records of Pteridophytes for Kashmir Valley, India. Biodiversitas 15: 131-136. During the recent field survey of district Shopian four species of Pteridophytes are reported for the first time that constitutes new recordsfor Kashmir valley. These species are Hypolepis polypodioides (Blume) Hook, Pteris stenophylla Wall. ex Hook. & Grev., Dryopterissubimpressa Loyal and Dryopteris wallichiana (Spreng.) Hylander. The diagnostic features of H. polypodioides are presence of longcreepingslender rhizome and eglandular, colorless or brown tinged hairs throughout the frond. P. stenophylla is characterized by havingdimorphic fronds and 3 to 5 pinnae clustered at stipe apex. D. subimpressa is marked by pale-green lamina and the largest basiscopicbasal pinnule in the lowest pair of pinnae. Similarly, the characteristic features of D. wallichiana are presence of huge frond size,glossier and dark-green lamina and dense browner scales in stipe and rachis. In present communication taxonomic description,synonyms, ecology and photographs are provided for each of these newly recorded species.